The social multiplier and labour market participation of mothers - Eric Maurin; Julie Moschion (Institute for the Study of Labor (IZA), 2006)
A mother's decision to participate in the labour market is correlated with those of the other mothers living in the same neighbourhood. This paper studies the extent to which this is causal. An identification problem exists because mothers with similar characteristics are often observed living in close proximity. Our identifying strategy uses instrumental variables. Specifically, the sex of the eldest siblings of the other mothers living in the neighbourhood is used as an instrument to identify the effect of neighbours' participation in the labour market on own participation. The IV estimate suggests a strong elasticity of own participation to neighbours participation. Interestingly enough, estimates using the quarters of birth of the children of the other mothers living in the neighbourhood as instruments are as large as estimates using the sex-mix instruments. We provide additional evidence showing that the random fertility shocks that affect the timing of births and the participation in the labour market of a mother, affect the participation in the labour market of the other mothers in the neighbourhood too.
urn:nbn:de:101:1-2008050513
Keywords: 330